Evaluation of a pharmacist-driven rapid infusion rituximab conversion protocol at a multisite cancer center. (December 2021) - Moore, Donald C; Gebru, Tsion; Plesca, Dragos
Introduction: Infusion-related reactions (IRR) are a common adverse event associated with rituximab, an anti-CD20 monoclonal antibody indicated for the treatment of B-cell lymphomas. IRR risk is highest with the first infusion, which is given by a slow titration over an average of 3.5 hours. Subsequent administrations can be given over an accelerated, rapid 90-minute infusion if patients meet specific criteria. To improve rapid infusion rituximab utilization, we developed and implemented a pharmacist-driven protocol which allows pharmacists to change the administration instructions to rapid infusion. Methods: A retrospective chart review was conducted to evaluate patients age ≥18 years with B-cell lymphomas who were eligible to receive rapid infusion rituximab following protocol implementation. The primary outcome was the prevalence of the use of rapid infusion rituximab for eligible patients. Secondary outcomes included the frequency of pharmacist-initiated conversions to rapid infusion rituximab and incidence of IRR with rapid infusions. Results: A total of 180 patients were included in this study; 89 patients in the pre-protocol group and 91 patients in the post-protocol group. Fifteen patients and 66 patients in the pre-protocol and post-protocol groups, respectively, received rapid infusion rituximab (17% vs. 73%, p < 0.00001). The pharmacist-driven protocol was used to convert 49 patients (54%) to rapid infusion. No IRR occurred in patients receiving rapid infusion rituximab. Conclusion: The implementation of a pharmacist-driven protocol led to a significant improvement in the use of rapid infusion rituximab and optimized chair time utilization at our institution.